Overemployment, executive pay-for-performance sensitivity and economic consequences: Evidence from China - Donghua Chen; Yongjian Shen; Fu Xin; Tianqin Zhang (China Journal of Accounting Research, 2012)
Using a sample of state-owned enterprises (SOEs) listed on the Shanghai and Shenzhen Stock Exchanges during the 1999-2009 period, we investigate the effects of overemployment on executives' pay-for-performance sensitivity (PPS) and analyze how the behavior of firms with high/low PPS affects the number of surplus employees. We find the existence of a redundant workforce significantly weakens PPS and the role of accounting measures in performance assessment. In contrast to prior literature, we find that higher PPS is associated with a stronger incentive to lay off redundant employees and to limit future employee numbers. We also find that weaker government intervention strengthens managerial control over the future size of the workforce. Finally, our findings suggest that a heavier government policy burden on SOEs leads to lower tax rates and more government gains.
Keywords: G38; J31; M48; 650; Government intervention; Surplus labor force; Pay-for-performance sensitivity; Policy burden; Policy gains